2017
DOI: 10.1007/s10803-017-3227-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Unusual Sensory Behaviors in Infants at Risk for, and Teens with, Autism Spectrum Disorder

Abstract: The current study investigated the prevalence and pattern of unusual sensory behaviors (USBs) in teens with Autism Spectrum Disorder (ASD) and infants (3-36 months) at risk for ASD. From two different sites (UCSD and UConn), caregivers of infants at high (n = 32) and low risk (n = 33) for ASD, and teenagers with (n = 12) and without ASD (n = 11), completed age-appropriate Sensory Profile questionnaires (Infant/Toddler Sensory Profile; Dunn 2002; Adolescent/Adult Sensory Profile; Brown and Dunn 2002). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The complex, multisystem nature of ASD along with its co‐occurring comorbidities requires children with ASD to access various medical, therapeutic, and mental health services (American Psychiatric Association, 2013 ; Bhat, 2020 , 2021 ; Bhat et al, 2011 , 2018 ; Shield et al, 2017 ; van Etten et al, 2017 ). Children with ASD utilize substantially more healthcare and therapeutic services compared to children with other disabilities or no disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The complex, multisystem nature of ASD along with its co‐occurring comorbidities requires children with ASD to access various medical, therapeutic, and mental health services (American Psychiatric Association, 2013 ; Bhat, 2020 , 2021 ; Bhat et al, 2011 , 2018 ; Shield et al, 2017 ; van Etten et al, 2017 ). Children with ASD utilize substantially more healthcare and therapeutic services compared to children with other disabilities or no disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the diagnostic symptoms, children with ASD also exhibit a variety of other impairments within the sensorimotor domain that may lead to significant challenges in their activities of daily living ( 18 26 ). Although the exact prevalence estimates of motor impairments in ASD vary widely across studies from around 35% to over 85%, there is a growing consensus that children diagnosed with ASD exhibit motor impairments in gross and fine motor skills (e.g., bilateral coordination, gait and postural stability, handwriting, manual dexterity skills, and visuomotor control), as well as socially-embedded motor skills, including imitation, praxis (performance of skilled functional movement sequences/gestures), and interpersonal synchrony (ability to synchronize movements with those of another person) ( 19 , 22 , 27 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prospective longitudinal studies comparing AR infants to typically developing (TD) infants without a family history of ASD can help in identifying early markers of ASD and other developmental delays and have important implications for the initiation of early intervention services (Fein et al, ). Past work including our own research has identified atypicalities and delays in the perceptuomotor domain including excessive visual exploration, poor grasping, immature postural control, poor use of motor skills during early infant–caregiver interactions, and an overall diminished movement repertoire in AR infants (Bhat, Galloway, & Landa, ; Flanagan, Landa, Bhat, & Bauman, ; Focaroli, Taffoni, Parsons, Keller, & Iverson, ; Kaur, Srinivasan, & Bhat, ; Koterba, Leezenbaum, & Iverson, ; Landa & Garrett‐Mayer, ; LeBarton & Iverson, ; Libertus, Sheperd, Ross, & Landa, ; Nickel, Thatcher, Keller, Wozniak, & Iverson, ; Ozonoff et al, ; Srinivasan & Bhat, ; van Etten et al, ). In the current study, we extend this line of research to another early emerging skill, namely, object retrieval.…”
Section: Introductionmentioning
confidence: 99%